2015
DOI: 10.3389/fnana.2015.00001
|View full text |Cite
|
Sign up to set email alerts
|

The spino-bulbar-cerebellar pathway: organization and neurochemical properties of spinal cells that project to the lateral reticular nucleus in the rat

Abstract: In addition to classical spinocerebellar pathways, the cerebellum receives information from the spinal cord indirectly via spino-bulbar-cerebellar systems. One of the structures in this pathway is the lateral reticular nucleus (LRt). We performed series of experiments to investigate the organization and neurotransmitter content of spinoreticular tract (SRT) neurons in the lumbar spinal cord that project to the LRt. Three rats received injections of the b subunit of Cholera toxin (CTb) or Fluorogold (FG) within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(85 citation statements)
references
References 47 publications
3
81
1
Order By: Relevance
“…29,30 Pertinent to our study are expression and sensitivity of TRPM8 because Quallo et al 7 demonstrated that TRPM8 is a neuronal osmo-sensor that regulates blinking in mice. Alamri et al 31 demonstrated that approximately 45% of corneal afferent neurons expressed TRPV1, 28% expressed Piezo2 (a marker of putative pure mechano-nociceptors), and 8% expressed TRPM8, with 6% of TRPV1 neurons coexpressing TRPM8 (a marker for of cold-sensing neurons); TRPM8 cold-sensing neurons are activated by menthol and hyperosmotic stimuli. 7,32 Our studies confirm that sensory nerves in the subepithelial layer and nerves penetrating the epithelial layer of the cornea express TRPM8.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Pertinent to our study are expression and sensitivity of TRPM8 because Quallo et al 7 demonstrated that TRPM8 is a neuronal osmo-sensor that regulates blinking in mice. Alamri et al 31 demonstrated that approximately 45% of corneal afferent neurons expressed TRPV1, 28% expressed Piezo2 (a marker of putative pure mechano-nociceptors), and 8% expressed TRPM8, with 6% of TRPV1 neurons coexpressing TRPM8 (a marker for of cold-sensing neurons); TRPM8 cold-sensing neurons are activated by menthol and hyperosmotic stimuli. 7,32 Our studies confirm that sensory nerves in the subepithelial layer and nerves penetrating the epithelial layer of the cornea express TRPM8.…”
Section: Discussionmentioning
confidence: 99%
“…The AF extending to the midtemporal cortex may be relevant to the evolution of language in the human brain because this pathway is absent in nonhuman primates [Rilling et al, 2008]. In addition, this pathway is more dominant in the left hemisphere than the right hemisphere in the healthy human brain [Catani et al, 2007; Takaya et al, 2015]. Our results indicate that the AF extending to the midtemporal cortex, which may play a substantial role during language-related processing in the healthy human brain, is likely to be affected in patients with left TLE.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the left inferior prefrontal cortex, including Broca’s area, may serve as a central executive for retrieving and evaluating semantic information and making decisions, presumably via top-down signals to the temporal cortex [Badre et al, 2005; Binder et al, 1997; Bookheimer, 2002; Demb et al, 1995; Thompson-Schill et al, 1997; Wagner et al, 2001; Whitney et al, 2011]. In particular, the semantic classification task requires functional interaction between Broca’s area and the left midtemporal cortex, supposedly through the AF [Demb et al, 1995; Glasser and Rilling, 2008; Takaya et al, 2015; Wang et al, 2014; Whitney et al, 2011]. In the current study, structural and task-modulated functional connectivity with Broca’s area decreased in the left midtemporal cortices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations